Has the NHS 111 urgent care telephone service been a success? Case study and secondary data analysis in England. Issue 5 (2nd June 2017) - Pope, Catherine; Turnbull, Joanne; Jones, Jeremy; Prichard, Jane; Rowsell, Ali; Halford, Susan
Abstract : Objectives: To explore the success of the introduction of the National Health Service (NHS) 111 urgent care service and describe service activity in the period 2014–2016. Design: Comparative mixed method case study of five NHS 111 service providers and analysis of national level routine data on activity and service use. Settings and data: Our primary research involved five NHS 111 sites in England. We conducted 356 hours of non-participant observation in NHS 111 call centres and the urgent care centres and, linked to these observations, held 6 focus group interviews with 47 call advisors, clinical and managerial staff. This primary research is augmented by a secondary analysis of routine data about the 44 NHS 111 sites in England contained in the NHS 111 Minimum Data Set made available by NHS England. Results: Opinions vary depending on the criteria used to judge the success of NHS 111. The service has been rolled out across 44 sites. The 111 phone number is operational and the service has replaced its predecessor NHS Direct. This new service has led to changes in who does the work of managing urgent care demand, achieving significant labour substitution. Judged against internal performance criteria, the service appears not to meet some targets such as call answering times, but it has seen a steady increase in use over time. Patients appear largely satisfied with NHS 111, but the view from some stakeholders is more mixed. The impact of NHS 111 on other health services is difficult to assess and cost-effectiveness has not been established. Conclusion: The new urgent care service NHS 111 has been brought into use but its success against some key criteria has not been comprehensively proven.